Leveraging Digital Communication Technology to Reduce Stunting: Evidence from the e-HDW Application in Bengkalis District, Riau Province - Indonesia - Chelsy Yesicha; Suyanto; Nurjanah; Ismandianto; Tutut Ismi Wahidar (Ikatan Sarjana Komunikasi Indonesia, 2025)
Stunting remains a critical public health issue in Indonesia, particularly in underdeveloped areas such as Bengkalis District. This study aims to analyze the effectiveness of communication strategies—specifically the implementation of the e-HDW (Human Development Worker) application—in reducing stunting prevalence, grounded in the Diffusion of Innovation theory and Health Belief Model to understand technology adoption and behavior change processes. This research applied a descriptive qualitative case study approach involving structured questionnaires, interviews, and documentation. Informants included local government officials, healthcare workers, and Human Development Cadres (KPM). The main outcome measured was the effectiveness of the e-HDW communication tool in increasing knowledge and adoption of stunting prevention behavior at the community level. The results indicate that the e-HDW application facilitated real-time nutrition monitoring and enhanced cross-sector collaboration, contributing to a measurable decline in stunting prevalence from 21.9% (2021) to 12.6% (2024). This supports previous findings that digital health interventions can significantly improve public health outcomes when combined with community-based communication strategies. The findings align with the theoretical framework, showing that communication agents like KPM accelerated technology adoption and behavior change. In conclusion, the e-HDW app is not merely a technical tool but an effective communication platform that fosters awareness, behavioral change, and inter-agency coordination. This study highlights the strategic role of communication technology in public health interventions and suggests replicability for similar contexts across Indonesia.